Supernatural Warnings: The Role Of Hantu Kopek, Wewe Gombel, And Ame-onna In Addressing Child And Family Issues - Ahmad Muhyiddin B Yusof; Ding DongLiang; Nasirin Abdullah; Mohd Muzhafar Idrus; Mohamad Hanis Bin Yahaya; Imran Danial Krish Bin Abdullah (Research & Scientific Innovation Society, 2025)
Indexed by WOS/Scopus/ERA/MyCite